IMPLIKASI PUTUSAN MAHKAMAH KONSTITUSI NOMOR:46/PUU-VIII/2010 TERHADAP PUTUSAN PENGADILAN AGAMA KEBUMEN TENTANG STATUS ANAK LUAR KAWIN - Saif Adli Zamani; Fransisca Romana Harjiyatni; Stefano Bintang Jati Asmoro (Fakultas Hukum Universitas Janabadra, 2023)
This paper aims to: 1) find out the implications of Constitutional Court Decision Number: 46 / PUU-VIII / 2010 on the Kebumen Religious Court Decision on the Status of Extramarital Children, and 2) find out how the Kebumen Religious Court Judges consider giving decisions on the status of extramarital children. This type of research is normative or doctrinal legal research. The research method uses a qualitative approach. The technique of collecting legal materials is carried out through literature studies and interviews. The interview was conducted with three judges at the Kebumen Religious Court, including: a) Mr. Drs. H. M. KAHFI, S.H., M.H., as the Chairman of the Kebumen Religious Court, b) Mrs. FITHRIATI AZ, S.Ag., as Vice Chairman of the Kebumen Religious Court; and c) Mr. Drs. H. ASRORI, S.H., M.H., as the First Instance Judge of Class IA. The results showed that, One Implication of the Constitutional Court Decision Number: 46/PUU-VIII / 2010 on the Kebumen Religious Court Decision on the Status of Unmarried Children, the Religious Court has new guidelines or jurisprudence in receiving, examining, prosecuting, and deciding cases related to the status of children out of wedlock, for example, the case of the origin of children. That a child born out of legal wedlock is entitled to legal certainty and justice, as well as legal certainty regarding the status of a child born in a legal marriage (legal child) that is recognized by the state that the extramarital child not only has a civil relationship with his mother, or his mother's family, but can also be listed as a man as his father who can be proven based on science and technology and or other evidence that according to the law, he is related by blood, including civil relations with his father's family. Two. The consideration of the Judge of the Kebumen Religious Court in Giving a Decision on the Status of Extramarital Children is that there are various opinions of judges related to this matter; there are judges who make serial marriage an absolute requirement so that children out of wedlock can be said to be legal children, and there are also judges who do not make serial marriage a benchmark so that the child is said to be his child, as long as it can be proved with science and technology that the child is his biological child.